# How do you solve #3(a + 2) + 5 = 2a + 4 #?

The solutions is

I hope this was helpful. That's the solution.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 3(a + 2) + 5 = 2a + 4, follow these steps:

- Distribute the 3 on the left side of the equation: 3(a + 2) = 3a + 6.
- Combine like terms on the left side: 3a + 6 + 5 = 3a + 11.
- Set the left side equal to the right side: 3a + 11 = 2a + 4.
- Subtract 2a from both sides: 3a - 2a + 11 = 2a - 2a + 4, which simplifies to a + 11 = 4.
- Subtract 11 from both sides: a + 11 - 11 = 4 - 11, which simplifies to a = -7.

Therefore, the solution to the equation 3(a + 2) + 5 = 2a + 4 is a = -7.

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7